Plasma Dynamics Using Ion Doppler Spectroscopy in HIT-SI3 - Hooper, Charles Thomas (My University, 2019)
The HIT-SI3 experiment uses three inductive helicty injectors to form and sustain a spheromak plasma by imposed-dynamo current drive (IDCD). An ion Doppler spectrometer utilizes 72 viewing chords and a $\mu$s time resolution to measure CIII impurity ions on the toroidal midplane. A Monte Carlo numerical routine is employed in conjunction with an Abel-inversion algorithm to gain insight into radial equilibrium profiles after ion spin up. Axi-symmetric ion flow is calculated from the geometric axis to the inner wall along the major radius for relative density, temperature, and ion flow velocity. The profiles are then compared to magnetohydrodynamic (MHD) simulation. Time-dependent analysis show coherent sinusoidal bulk motion that is locked to the frequency of the injector perturbations indicating spheromak stability. There is evidence for ion motion in the opposite direction as the electron current in the outer injector-driven region and an ion flow reversal in the spheromak region. Relative electron density is approximately uniform from the geometric axis moving radial outwards and rapidly peaking after the magnetic axis near major radius R=45.5 cm, in the same region as the maximum ion temperature.
Thesis (Master's)--University of Washington, 2019
Keywords: Plasma physics; Aerospace engineering; Aeronautics and astronautics